MENINGKATKAN HASIL BELAJAR IPA MELALUI MODEL HANDS ON ACTIVITY PADA MURID KELAS V SD MUHAMMADIYAH 1 BONTOALA MAKASSAR - Yeni Marnia; Khaeruddin; Rahmatiah Thahir (Nusantara Hasana Journal, 2023)
Science subjects are subjects related to systematic methods for learning about nature. The study of natural phenomena is the focus of the scientific discipline. In an elementary school science class, students learn about close natural knowledge. In previous studies, many students did not understand science lessons with the material "tot disorders in humans". Students had never heard of any muscle abnormalities in humans. after that students ask a lot of what tetanus is and what causes it, educators provide material about muscle disorders in humans and students read every material provided by educators after that they understand better what abnormalities occur in humans. Fifth grade students at SD MUHAMMADIYAH 1 BONTOALA have shown that the use of hands-on activity models can improve science learning outcomes. This is shown in the pre-cycle learning outcomes, namely 38 with the predicate "poor", the first cycle is worth 67 with the predicate "enough", and the second cycle is worth 96 with the predicate "good" with a performance indicator of 70.